Hamuramicins A and B, 22-membered macrolides, produced by an endophytic actinomycete Allostreptomyces sp. K12-0794. (July 2018) - Suga, Takuya; Kimura, Tōru; Inahashi, Yuki; Iwatsuki, Masato; Nonaka, Kenichi; Také, Akira; Matsumoto, Atsuko; Takahashi, Yōko; Ōmura, Satoshi; Nakashima, Takuji
Abstract Two new compounds, designated as hamuramicins A (1 ) and B (2 ), were isolated from the cultured broth of an endophytic actinomyceteAllostreptomyces sp. K12-0794 by silica gel column chromatography and HPLC. The structures of1 and2 were elucidated as 22-membered macrolide containing triene and trienone with an alkyl side chain by spectroscopic analyses including NMR experiments. Both compounds showed growth inhibition activity againstKocuria rhizophia andXanthomonas oryzae pv.oryzae as well as human cell line toxicity.